GIS-based approach for flood analysis: case study of Keçidere flash flood event (Turkey). Issue 4 (20th April 2016) - Curebal, Isa; Efe, Recep; Ozdemir, Hasan; Soykan, Abdullah; Sönmez, Süleyman
Abstract : The purpose of this study is to explain the formation mechanism of the floods which occurred in the Keçidere basin in 2009. In this study, discharge data in between 1981 and 2009, digital elevation model (DEM), satellite images and field works were used as a main data sources. LPT3 was applied to 29-year maximum flow data to produce different flood return periods such as 2, 5, 50, 100, 200, 500 and 1000-year flood. The DEM was created using 1:25, 000 topographic contours with Topo to Raster interpolation techniques in geographical information systems (GIS). Land use and some geometric data were digitized using high resolution satellite images for hydraulic modelling purposes. Simulation of the 2009 flash flood event and different return periods flow data was done using one-dimensional hydraulic modelling with HEC-RAS. In the last phase, results obtained from the simulations and field works were compared based on fits statistics and mean absolute error in terms of extent and depth. An analysis of water extent and depth features observed during the highest flow ever measured in the basin revealed that the result overlapped with 500-year inundation extent. Overall, the results of the research indicate that GIS is an effective environment for floodplain mapping and analysis.